Disclosing or concealing multiple sclerosis in the workplace: two sides of the same coin—insights from a Swedish population-based survey - Dervish, Jessica; Arfuch, Victoria Mailen; Murley, Chantelle; McKay, Kyla A.; Machado, Alejandra; Wennman-Larsen, Agneta; Friberg, Emilie (Frontiers in Public Health, 2024)
Background: People with multiple sclerosis (PwMS) face health and social challenges of living with a chronic and potentially disabling condition. To disclose or conceal MS at work may critically affect individuals’ work situation, career opportunities, and health. PwMS may experience a dilemma when assessing if the possible benefits of disclosing the diagnosis outweigh the possible risks. However, concealing in the long-term may have health implications and prevent opportunities for support and work adjustments. Few studies have examined what drives PwMS to disclose or conceal MS at work and the consequences of these ways of managing MS. Objectives: To explore the reasons PwMS report for disclosing and/or concealing their MS diagnosis in the workplace, as well as the consequences they have experienced. Methods: A web-based survey of PwMS was conducted in 2021. All individuals aged 20-50 listed in the Swedish MS registry were invited to participate. The response rate was 52% and among these participants, 3810 (86%) completed questions regarding workplace disclosure and/or concealment of MS. Free-text responses on these topics were analyzed using inductive content analysis. Results: It was common to disclose MS in the workplace (85%). Identified drivers for disclosure and concealment related to four categories: Work-related, Social, Personal and Circumstantial. Work-related drivers focused on employment or protecting one’s career, and changing one’s work situation versus maintaining it. Social drivers included the need for support, addressing or preventing stigma, and being considerate of others. Personal drivers were linked to moral values/personal beliefs and processing of the diagnosis. Circumstantial drivers related to involuntary or unforeseen events, timing factors, one’s medical condition and external opinion/advice. Identified consequences for disclosure and concealment related to three categories: Work-life, Social, and Personal. Work-life consequences included work arrangements, and career opportunities. Social consequences were linked to MS awareness, stigma, interactions and social support, as well as dynamics of work relationships. Personal consequences involved levels of disease acceptance, and attitudes towards managing MS. Conclusion: PwMS often described the question of disclosure as challenging and navigated it with caution, as both disclosure and concealment can yield favorable and unfavorable outcomes.